Fundamentos do serviço social : um estudo a partir da produção da área - Closs, Thaísa Teixeira (2015)
This thesis systematize a study on the Foundations of Social Work, based on the marxist social theory, analyzing how they compose and are expressed in the production of knowledge of the area, in its conceptuals dimensions and mediations in the field of training and professional practice. It was developed from quantitative and qualitative study that analyzed the productions published in 11 academic journals of the field in the last two decades (1993-2013), totaling 2031 articles reviewed, forming a database composed of 324 articles that have keywords related to Foundations of Social Work. It was verified that the production that directly addresses the Foundations is quite small, not reaching 1% of the publications of academic journals (0.49%) and that the totality of articles dealing with issues relating to Foundations is also reduced (15.91%). The set of quantitative and qualitative data obtained from the survey shows that there is a predominance of an approach of the Foundations by emphasizing the historicity and professional work, axis that concentrate the highest quantitative universe productions, followed by papers on theory / method / marxism and social issue. At the end of the study, we arrive at the following thesis, which synthesize the main conclusions of the investigative route: The Foundations of Social Work consist of explanatory matrix of reality and the profession, particular to the Social Work, (re) built procedurally in its historical trajectory the movement of the Brazilian reality, which has theoretical and methodological dimensions and ethical-political underlying the technical and operational dimension of this profession.This matrix, today, compose itself from the combination of marxist method / theory and emancipatory values in the historical-critical analysis totalizing of Social Work profession whose core lies in the marxist theoretical-methodological debate, in the analysis of its historicity, in theoretical approach of social issues and the work category (mediated with the profession), as well as their ethical-political project. The small direct dealing and scarce visibility of the Foundations in the production area reveals a contradiction in process between the totalizing conceptual densification of this matrix and the systematization of a field of mediation and particularities that contribute to its materialization in the field of training and professional practice in a regressive society conjuncture of capital offensive over work, the struggles and social rights that impacts on own historical hegemony basis of this matrix and also weakens this conjugation.